The Influence of Education Level, Age and Work Experience on the Productivity of Employee Workforce at the Selaparang District Office, Mataram City - Dea Farlingga Feny; Gusti Ayu Arini; Ahmad Zaenal Wafik (Indonesian Development Economics and Localities, 2025)
The purpose of this study was to analyze the effect of education level, age, and work experience on employee work productivity at the Selaparang District Office, Mataram City. The population in this study were all employees at the Selaparang District Office, Mataram City, totaling 31 people, consisting of 20 PNS, 1 PPPK, and 10 Non ASN. This study used the census method as a data collection method, with data collection techniques in the form of questionnaires and literature studies. The analysis techniques used were the Likert scale and Eviews 12 software, with multiple linear regression analysis methods, determination coefficient test (R²), t test (partial), and F test (simultaneous). The results showed that the variables of education level, age, and work experience simultaneously had a significant effect on employee work productivity at the Selaparang District Office, Mataram City. The coefficient of determination (R2) value was 0.62, which means that the three independent variables in the model can explain the variation in work productivity by 62%, while the remaining 38% was influenced by other variables outside this research model.